From androcentrism to ecofeminism: Gary Snyder's Goddess worship. (5th November 2021) - Qiu, Yan
Abstract: Hailed as the "poet laureate of Deep Ecology, " Gary Snyder frequently depicts various goddesses derived from both the Eastern culture and the Western culture in his works. The resurrection of the divine feminine imagery in his poetic and prose works reflects his consciousness of Goddess worship. This essay, from a diachronic perspective, examines Snyder's Goddess worship and argues that his psychological journey to ecofeminism is roughly divided into three phases: androcentrism, feminism, and ecofeminism. It aims to reveal the transformative process and how it has led to Snyder's acceptance of ecofeminism; the essay will also demonstrate the internal causality between his worship of the Goddess and his ecological consciousness. The psychological changes of Snyder's reverence for the Goddess, in a way, mirror the historical evolution of gender relations.